LIVING MUSEUM: AN EMERGING STRATEGY DERIVED FROM THE 7P MARKETING MIX FO THE MUSEUM KETRANSMIGRASIAN LAMPUNG - Adi Asmariadi Budi; Nazdan; Annisa Yulyana Pibiand (Proceedings International Indonesia Conference on Interdisciplinary Studies, 2025)
The Museum Ketransmigrasian Lampung, established in 2004 and owned by the Government of Lampung Province, is the only museum in the world dedicated to the theme of transmigration. It is located in Bagelen Village - the first site of transmigration initiated by the Dutch East Indies, which is now part of Indonesian territory. As a government institution, the museum also serves a commercial function by charging an admission fee to visitors. In its ongoing development, the museum requires a strategic approach to ensure its relevance and competitiveness within the broader landscape of museums and tourist attractions. This study aims to formulate a development and commercialization strategy for the Museum Ketransmigrasian Lampung. A qualitative methodology employing the 7P marketing mix framework (product, price, promotion, place, people, process, and physical evidence) was utilized to construct the strategic model. The analysis generated detailed strategies for each of the 7P elements, culminating in the emergence of a comprehensive strategy that positions the concept of a “living museum” as both the brand identity and the core strategic direction for the Museum Ketransmigrasian Lampung. Based on the findings, this study recommends that the Government of Lampung Province adopt and implement the “living museum” concept as a central element in the museum’s program planning and development.